Biased estimations of interpersonal distance in non-clinical social anxiety. (January 2020) - Givon-Benjio, Nur; Okon-Singer, Hadas
Highlights: Social anxiety is characterized by a preference for greater distance from strangers. This distance preference is predicted by biased distance estimation from strangers. These results were replicated and validated in a real-life setting scenario. Avoidance behavior in social anxiety may be related to biased distance estimation. Abstract: Previous studies have indicated that socially-anxious individuals prefer to maintain a greater interpersonal distance from others, specifically from strangers. Notwithstanding, it has yet to be examined whether this preference for distance is associated with estimating the physical interpersonal distance in a distorted manner. In the current study, 100 participants performed a computerized task that measured estimated distance (Study 1). An additional sample of 75 participants performed the same task for the purpose of replication, and further took part in a new task that measured estimated distance from a stranger in a real-life setting (Study 2). In both studies social anxiety correlated with estimating the interpersonal distance from strangers as shorter. Furthermore, ones' preferred distance from a stranger was predicted by this distance estimation bias. Taken together, our findings are the first to reveal distance estimation bias in social anxiety, suggesting a role for distorted distance estimation in avoidance behavior.